Increased testing is needed for Mpox in DR Congo to urgently curb disease spread - Prince Imani-Musimwa; Placide Mbala-Kingebeni; Stéphane Hans-Bateyi-Mustafa; Alfred Ombeni-Musimwa; Mija Ververs (Communications Medicine)
The low testing rates of Mpox suspected cases remain a key factor in the continued spread of the disease in the Democratic Republic of Congo (DRC) and neighboring countries. Here, we highlight the causes, as well as the challenges and strategies needed to curb the spread of the current uncontrolled Mpox outbreak in the DRC.